Validating the Civic-Minded Graduate Scale in Engineering Education Using Mixed Methods - Athena Lin; Justin L Hess (Michigan Journal of Community Service Learning)
Civic-mindedness is a central aim of higher education, but strategies for assessing civic-mindedness in engineering education are limited. Thus, engineering educators must build on strategies employed across higher education while ensuring these strategies are transferable to the engineering context. This study continues ongoing validation work of the Civic-Minded Graduate Scale in engineering by using mixed methods to pursue multiple forms of validity evidence. We collected, analyzed, and triangulated findings from first-year engineering students using 419 survey responses and 11 semi-structured interviews. We integrated quantitative and qualitative data to evaluate how the five constructs of the Civic-Minded Graduate Scale represent engineering students’ civic-mindedness and manifest in engineering students’ perceptions of the engineering profession. We align our data with existing engineering education research, particularly in the domains of ethics, humanitarian engineering, and professional skills development. We close with implications for teaching and assessing civic-mindedness within and outside of engineering education.